ANALISIS MISKONSEPSI SISWA PADA MATERI PERSAMAAN GARIS LURUS MENGGUNAKAN THREE TIER-TEST DITINJAU DARI KEMAMPUAN AWAL SISWA - Mochammad Hilmy Manfaluthy; Yuyu Yuhana (Universitas Cokroaminoto Palopo, 2024)
This research aims to analyze students' misconceptions about straight line equations, using the Three Tier-Test instrument and interviews. This research has subjects, namely class VIII B students at SMPN 15 Serang City with a total of 19 students. This research resulted in: (1) Misconceptions experienced in each category of students' initial abilities. (2) The cause of a misconception faced by students. (3) How to overcome misconceptions faced by students.